2011
DOI: 10.1016/b978-0-12-544172-8.00008-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA Expression and Function

Abstract: Originally discovered in C. elegans, microRNAs (miRNAs) are small RNAs that regulate fundamental cellular processes in diverse organisms. MiRNAs are encoded within the genome and are initially transcribed as primary transcripts that can be several kilobases in length. Primary transcripts are successively cleaved by two RNase III enzymes, Drosha in the nucleus and Dicer in the cytoplasm, to produce ~70 nucleotide (nt) long precursor miRNAs and 22 nt long mature miRNAs, respectively. Mature miRNAs regulate gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 81 publications
2
48
0
Order By: Relevance
“…Increasing evidence shows that many cellular processes, including proliferation, apoptosis, and cytokine release, are regulated by miRNAs that are 19-25 nt in length [45]. Thus, miRNAs have considerable potential to become a research focus for prevention and treatment of IDD, especially for targeting IDD-related cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that many cellular processes, including proliferation, apoptosis, and cytokine release, are regulated by miRNAs that are 19-25 nt in length [45]. Thus, miRNAs have considerable potential to become a research focus for prevention and treatment of IDD, especially for targeting IDD-related cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs carry out functions by negatively regulating translation of specific mRNAs. (29) We explored the effects of miR-93 on Sp7. As a result, overexpression of miR-93 only decreased the expression of Sp7 protein but not mRNA, which suggested that miR-93 regulated osteoblast mineralization via suppressing Sp7 at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Micro RNAs are short (22 nucleotides) singlestranded RNAs that post-transcriptionally regulate gene expression by binding to imperfect complementary sites within the 3 0 -UTRs of their mRNA targets (Van Wynsberghe et al 2011). In view of our results, it would be worthwhile to explore in future studies if AbOs treatment increases microRNA Let-7d levels in primary hippocampal neurons.…”
Section: Discussionmentioning
confidence: 86%